Silver nanoparticle probe for colorimetric detection of aminoglycoside antibiotics: picomolar‐level sensitivity toward streptomycin in water, serum, and milk samples. (10th December 2019) - Ghodake, Gajanan; Shinde, Surendra; Saratale, Rijuta Ganesh; Kadam, Avinash; Saratale, Ganesh Dattatraya; Syed, Asad; Marraiki, Najat; Elgorban, Abdullah M.; Kim, Dae‐Young
Abstract: BACKGROUND: The low cost of aminoglycoside (AMG) antibiotics facilitates their excessive use in animal husbandry and the agriculture sector. This scenario has led to the occurrence of residues in the food chain. After several years of AMG use in antibacterial therapy, resistance to streptomycin has begun to appear. Most of the detection methods developed for AMG antibiotics lacks specificity. A broad target specific nanoprobe would be ideal for detecting the entire class of AMGs. A rapid and sensitive method for the detection of AMGs is urgently needed. RESULTS: Gallic acid‐coated silver nanoparticles (AgNPs) were demonstrated as a nanoprobe for the colorimetric detection of AMGs (yellow to orange / red). A linear dynamic range of 50–650 pmol L −1 was achieved readily by ratiometric spectrophotometry (A560 /A400 ) with a limit of detection (LOD) as low as 36 pmol L −1 . The amine‐groups of the AMGs function as molecular linkers, so that electrostatic coupling interactions between neighboring particles drive the formation of AgNP aggregates. The assay can also be applied for the determination of streptomycin residues in serum and milk samples. CONCLUSION: This study revealed the potential of an AgNP probe for the rapid and cost‐effective detection of low‐molecular‐weight target analytes, such as the AMGs. A ligand‐induced aggregation of AgNPs coated with gallic acid was reported to be a rapid and sensitive assay for AMGs. Analysis of streptomycin was demonstrated with excellent picomolar‐level sensitivity. Thus, the validated method can find practical applications in the ultrasensitive detection of AMGs in complex and diagnostic settings. © 2019 Society of Chemical Industry